The Gemini-North Multi-Object Spectrograph: Performance in imaging, long-slit, and multi-object spectroscopic modes - Hook, I; Jørgensen, I; Allington-Smith, JR; Davies, R; Metcalfe, N; Murowinski, R; Crampton, D (2004)
Results of the commissioning of the first Gemini Multi-Object Spectrograph (GMOS) are described. GMOS and the Gemini-North telescope act as a complete system to exploit a large 8 m aperture with improved image quality. Key GMOS design features such as the on-instrament wave-front sensor (OIWFS) and active flexure compensation system maintain very high image quality and stability, allowing precision observations of many targets simultaneously while reducing the need for frequent recalibration and reacquisition of targets. In this paper, example observations in imaging, long-slit, and multiobject spectroscopic modes are presented and verified by comparison with data from the literature. The expected high throughput of GMOS is confirmed from standard star observations; it peaks at about 60% when imaging in the r′ and i′ bands, and at 45%-50% in spectroscopic mode at 6300 Å. Deep GMOS photometry in the g′, r′, and i′ filters is compared to data from the literature, and the uniformity of this photometry across the GMOS field is verified. The multiobject spectroscopic mode is demonstrated by observations of the galaxy cluster A383. Centering of objects in the multislit mask was achieved to an rms accuracy of 80 mas across the 5′.5 field, and an optimized setup procedure (now in regular use) improves this to better than 50 mas. Stability during these observations was high, as expected: the average shift between object and slit positions was 5.3 mas hr -1, and the wavelength scale drifted by only 0.1 Å hr -1 (in a setup with spectral resolution of 6 Å). Finally, the current status of GMOS on Gemini-North is summarized, and future plans are outlined.